Non-Steroidal Anti-Inflammatory Drugs and Cognitive Function: Are Prostaglandins at the Heart of Cognitive Impairment in Dementia and Delirium ? - SKELLY, DONAL; CUNNINGHAM, COLM (My University, 2012)
Studies of non-steroidal anti-inflammatory drugs (NSAIDs) in rheumatoid arthritis imply that inflammation is important in the development of Alzheimer's disease (AD). However, these drugs have not alleviated the symptoms of AD in those who have already developed dementia. This suggests that the primary mediator targeted by these drugs, PGE2, is not actively suppressing memory function in AD. Amyloid-? oligomers appear to be important for the mild cognitive changes seen in AD transgenic mice, yet amyloid immunotherapy has also proven unsuccessful in clinical trials. Collectively, these findings indicate that NSAIDs may target a prodromal process in mice that has already passed in those diagnosed with AD, and that synaptic and neuronal loss are key determinants of cognitive dysfunction in AD. While the role of inflammation has not yet become clear, inflammatory processes definitely have a negative impact on cognitive function during episodes of delirium during dementia. Delirium is an acute and profound impairment of cognitive function frequently occurring in aged and demented patients exposed to systemic inflammatory insults, which is now recognised to contribute to long-term cognitive decline. Recent work in animal models is beginning to shed light on the interactions between systemic inflammation and CNS pathology in these acute exacerbations of dementia. This review will assess the role of prostaglandin synthesis in the memory impairments observed in dementia and delirium and will examine the relative contribution of amyloid, synaptic and neuronal loss. We will also discuss how understanding the role of inflammatory mediators in delirious episodes will have major implications for ameliorating the rate of decline in the demented population.
PUBLISHED
Keywords: Neuroscience; Immunology; Infection; Alzheimer?s disease (AD); Dementia; Delirium; Cyclooxygenase; Prostaglandin; Ageing; Immunology, Inflammation & Infection; Neuroscience